Remarkable thermal stability of Si-doped γ-Fe2O3 thin films - Seishi Abe (AIP Advances)
The thermal stability of Si-doped γ-Fe2O3 thin films was investigated. These films were prepared by using a two-step process. First, Si-doped Fe3O4 thin films were prepared on water-cooled glass substrates by radio frequency sputtering, followed by heat treatment in air for up to 256 days. X-ray diffraction patterns revealed that a mixed phase of Fe3O4 and α-Fe2O3 is formed in as-deposited state without Si addition, whereas a single phase of Fe3O4 is formed with Si addition. Subsequent annealing at 673 K in air resulted in rapid loss of magnetization for 0 at. % Si, whereas magnetization remained almost constant for 2.8 at. % Si even after 256 days of annealing. While the magnetization was maintained, the optical transmittance of the film tended to increase with heat treatment time, reaching ∼80% at 13 days and then remaining almost unchanged until the end of heat treatment (256 days). The increase in optical transmittance was attributed to the formation of iron vacancies in Fe3O4, whose activation energy was estimated to be 213 kJ/mol. Raman spectra showed that the sample was assigned to γ-Fe2O3 after heat treatment in air for 256 days, while the crystal structure remained unchanged after heat treatment. Hence, it was suggested that the Si-doped Fe3O4 thin film undergoes a phase transition to fully disordered cubic γ-Fe2O3 after heat treatment. The magnetization of the samples hardly decreased even at a relatively high temperature of 873 K in air for 53 days. Thus, the Si-doped γ-Fe2O3 that underwent the phase transition exhibits remarkable thermal stability.